Developing Mucous Penetrating Particles for Intestinal Gene Delivery using Non-viral GET Peptide System - Elnima, Alaa (2024)
Gene delivery to intestinal tissue would enable the treatment of several debilitating disorders, such as inflammatory bowel disease (IBD) effectively. Many extracellular and intracellular barriers limit the success of intestinal gene delivery systems including the mucus layer covering the gastrointestinal tract’s surface that regulates the diffusion of drugs to the intestinal epithelium membrane and exerts multiple barrier properties. Successful mucous-penetrating nanoparticles should carry contradictory surface properties, where negative charge avoids interaction and entrapment with mucus, while positive charge promotes cellular uptake. Various strategies have been implemented to solve this dilemma, including charge-changing systems and coating with hydrophilic mucus-inert polymers. In this project, these strategies are addressed by manipulation of a non-viral gene delivery platform of a novel cationic peptide named Glycosaminoglycan (GAG)-binding enhanced transduction (GET) system. GET system combines a GAG-binding domain for promoting cell binding and cell-penetrating peptide (CPP) for efficient cell entry and has demonstrated efficient intracellular delivery of different cargos to various cells. Herein, the potential of GET system in enhancing the gene delivery to intestinal tissue was assessed, followed by modification of GET system to develop mucus-penetrating particles with charge-changing features using phosphate-bearing ligands in the form of phospho-Tyrosine (pTyr) or with a potential hydrophilic muco-inert coating polymer of hydroxyethyl acrylamide and β-alanine acrylamide copolymer (HEA-co-βAA). A combination of an endosomal escape GET variant with 10 H units (termed FLH), and a cell-penetrating variant (termed FLR) was required to enhance the transfection efficiency in an in vitro intestinal model consisting of intestinal epithelial cells (Caco-2) and mucus-producing cells (HT29-MTX). Using p(pTyr) polymer as coating of DNA/GET NPs generated negatively charged NPs liable to enzymatic cleavage of their phosphate ester bond with calf intestinal phosphatase enzyme (CIP) as tested with green malachite assay. Those phosphorylated DNA/GET NPs demonstrated a charge reversal from ii negative to nearly neutral surface in the presence of CIP enzyme, but the phosphorylation of GET system significantly reduced the transfection efficiency. On the other hand, the HEA-co-βAA polymer demonstrated improved mucus penetration ability on different mucus models. The HEA-co-βAA-coated NPs showed minimum entrapment on the upper mucus layer of mucus-producing cells and exhibited less restricted trajectories and more diffused particles in porcine intestinal mucus using multiple particle tracking (MPT). The DNA/GET NPs coated with HEA-co-βAA polymer enhanced the transfection efficiency on mucus-producing cells and co-culture model of Caco-2 and HT29-MTX cells. In addition, those coated NPs were able to deliver hIL-10 vector into the co-culture model. The potential ability of this cationic peptide system (GET) to significantly promote pDNA delivery through an in-vitro intestinal model, together with its ability to modification for the purpose of enhancing mucus-penetration while maintaining its functionality could serve as an efficient tool for intestinal non-viral gene delivery.